The Multiband Imaging Survey for High-alpha PlanetS (MISHAPS). I. Preliminary Constraints on the Occurrence Rate of Hot Jupiters in 47 Tucanae - Alison L. Crisp; Jonas Klüter; Marz L. Newman; Matthew T. Penny; Thomas G. Beatty; L. Ilsedore Cleeves; Karen A. Collins; Jennifer A. Johnson; Marshall C. Johnson; Michael B. Lund; Clara E. Martínez-Vázquez; Melissa K. Ness; et al. (The Astronomical Journal)
The first generation of transiting planet searches in globular clusters yielded no detections, and in hindsight only placed occurrence rate limits slightly higher than the measured occurrence rate in the higher-metallicity Galactic thick disk. To improve these limits, we present the first results of a new wide-field search for transiting hot Jupiters in the globular cluster 47 Tucanae (47 Tuc). We have observed 47 Tuc as part of the Multiband Imaging Survey for High-Alpha PlanetS. Using 24 partial and full nights of observations taken with the Dark Energy Camera on the 4 m Blanco telescope at Cerro-Tololo Interamerican Observatory, we perform a search on 19,930 stars in the outer regions of the cluster. Though we find no clear planet detections, by combining our result with the upper limit enabled by R. L. Gilliland et al.’s Hubble search for planets around an independent sample of 34,091 stars in the inner cluster, we place the strongest limit to date on hot Jupiters with periods of 0.8 ≤ P ≤ 8.3 days and 0.5 R _Jup ≤ R _P ≤ 2.0 R _Jup of f _HJ < 0.11%, a factor of ∼4 below the occurrence rate in the Kepler field. Our search found 35 transiting planet candidates, though we are ultimately able to rule out each without follow-up observations. We also found four eclipsing binaries (EBs), including three previously uncataloged detached EB stars.